M. Grushevskiy and I. Nechuy-Levitsky: the history of creative relationships - Tereschenko, A. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. Life and work M.Grushevsky devoted hundreds of scholarly monographs and articles. However, further understanding of the creative heritage of outstanding Ukrainian, clarify the facts of his life continues to be an important task hrushevoznavstva. In this context it is relevant research and creative coverage of relations between the two leading figures of the Ukrainian national revival of the late nineteenth - early. Twentieth century. Mykhailo Hrushevskyi and I. Nechuy-Levitsky, last played a significant role in the development and shaping of literary talent of the future famous historian Ukraine. Purpose. Research is trying on new methodological approaches in the context of biographical and creative prosopography explore the history and relationships Grushevkiy I.Nechuy-Levitsky, reveal the role of the latter in the formation of the creative person, including literary skills, the future author of fundamental work «History of Ukraine-Rus» highlighting key periods of their relationship, to analyze factors of their complexity and contradictions. Results. Revealed that the history and creative relationship M.Grushevkiy I.Nechuy-Levitsky is quite controversial, which should be the history of relations of two extraordinary people and which highlight how the stages of mutual interest, mutual respect and sincere communication between an experienced writer, mentor and beletrystom- beginners business cooperation between the already well-known figures of the Ukrainian movement, and stage of ideological disputes between them. However, despite sometimes on some of its sharpness, M.Grushevskii left deference to I.Nechuy-Levitsky, as his literary mentor and dedication to the founder of Ukrainian literature, as evidenced by his memories. Originality. Scientific novelty of our study is an attempt to highlight the history of controversial relationships Grushevkiy creative and I.Nechuy-Levitsky. Conclusion. Overall Grushevkiy and creative relationship I.Nechuy Levitsky played a significant role in the development cultural Ukrainians, facilitating further development of the Ukrainian national liberation movement of the late nineteenth - early twentieth century. Testified ideological continuity between generations of Ukrainian intelligentsia, showing an example of faithful service interests Ukrainian people.